2020
DOI: 10.4236/wjns.2020.104021
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Parkinson’s-Disease-Linked Genes, Brain Urea Levels and Histopathology in Rotenone Induced Parkinson’s Disease Rat Model

Abstract: Parkinson's disease (PD) is a debilitating neurological disorder that affects the aged population globally. This study aimed to explore how oral-and intraperitoneal-rotenone-induced PD alters brain urea levels, histopathology, and key Parkinsonism-related genes in the striatum. Hematoxylin and eosin staining was performed for histopathology assessment and real-time polymerase chain reaction was performed for gene expression. Rotenone 3 mg/kg body weight (Rot-3-ip) for 21 days and rotenone 50 mg/kg body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The blood-brain barrier (BBB) is impermeable to urea; hence, increased brain urea levels in the present study indicate either increased synthesis of brain urea inside the central nervous system or breakage of BBB 54 . A similar experimental study on PD also suggests increased brain urea in Wistar rats induced with rotenone 37 .…”
Section: Urea Changes In Thementioning
confidence: 55%
See 1 more Smart Citation
“…The blood-brain barrier (BBB) is impermeable to urea; hence, increased brain urea levels in the present study indicate either increased synthesis of brain urea inside the central nervous system or breakage of BBB 54 . A similar experimental study on PD also suggests increased brain urea in Wistar rats induced with rotenone 37 .…”
Section: Urea Changes In Thementioning
confidence: 55%
“…36 . Current evidence suggests that intraperitoneally administered rotenone induces PD much earlier and efficiently with less mortality than orally administered rotenone does 37 .…”
Section: Fig 4: Comparative Effect Of High-fat Diet (Hfd) Rotenone (R...mentioning
confidence: 99%
“…Based on our preliminary published results, Kavuri et al, 2020 [21] , it was found that Rot-3-ip induction for 21 days in Wistar rats showed signi icant upregulation of α-synuclein expression (Immuno-histochemistry) with Lewy bodies in brain striatum; whereas Rot-50-po treatment for 28 days in rats caused a moderate increase of α-synuclein with no detectable Lewy bodies. The brain sections from the control groups showed normal architecture.…”
Section: Discussionmentioning
confidence: 83%
“…MTs exert various functions, such as in organelle and protein trafficking, cellular differentiation, cargo transport, and motility [ 190 , 191 ]. For a long time now, oxidative stress has been a major and constant culprit in PD pathogenesis, and this has been supported by several postmortem studies in PD brains showing increased levels of oxidative proteins, lipids and nucleic acids [ 192 196 ], as well as in studies of genetic or toxin-induced PD models[ 197 201 ]. In non-neuronal cells, researchers found that oxidative stress affects MT dynamics by hindering tubulin polymerization and hence affects its stability [ 202 204 ].…”
Section: Mt Acetylation Status In Pdmentioning
confidence: 99%